2015
DOI: 10.3906/bot-1401-66
|View full text |Cite
|
Sign up to set email alerts
|

Seed micromorphology in Dactylorhiza Necker ex Nevski (Orchidaceae)and allied genera

Abstract: were assigned to 3 different species groups in Delforge (2006).Nowadays, the inclusion of Coeloglossum viride (L.) Hartm. in the genus Dactylorhiza is generally accepted. This species has a holarctic-boreal distribution, extending from North America to Japan (Delforge, 2006). Morphologically, it is distinguished from the rest of the genus Dactylorhiza by the spur, which is short and nectariferous, and the petals and sepals, which are joined

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Hence, later correlations of these flotation times determined by Burgeff (1936) with seed mass and volume by Arditti and Ghani (2000) were not based on the same material. This may be problematic because at least some orchids show considerable intraspecific variation in seed length (Gamarra et al ., 2015). There are very few other determinations of V term for orchid seeds, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, later correlations of these flotation times determined by Burgeff (1936) with seed mass and volume by Arditti and Ghani (2000) were not based on the same material. This may be problematic because at least some orchids show considerable intraspecific variation in seed length (Gamarra et al ., 2015). There are very few other determinations of V term for orchid seeds, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Testa cells show a set of characteristics that have been observed under light and scanning electron microscopes, providing qualitative and quantitative data used to describe the seeds' morphology [2][3][4][5][6]. Previous studies on seed micromorphology have demonstrated the taxonomic value of several traits [7][8][9], and emphasize its strong correlation with molecular phylogenies [4,[10][11][12]. In Orchidaceae, seed traits are more conservative than other characteristics [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Its representatives are marked by a high phenotypic variability, which often complicates attempts of drawing borderlines between species even within the same or close plant communities (Naczk 2018 ;Averyanov 1990). These issues have been addressed variously on the basis of morphology (van Straaten 1988;Shipunov et al 2005a), micromorphology (Hedrén 2009;Gamarra et al 2015;Akbulut 2016) morphometry (Tyteca 1999;Pedersen 2002;Shipunov 2005b;Bateman 2006;Ashish 2012;Shirokov 2020), anatomy (Aybeke et al 2010), molecular biology (Bateman et al 2003;Shipunov et al 2004;Devos et al 2006;Pillon et al 2007;Inda et al 2010;Balao 2017), and molecular genetics (Givnish 2015;Efimov 2016;Bateman 2018aBateman , 2018bKakia 2020).…”
Section: Introductionmentioning
confidence: 99%